Utilizing Educational Technology as a Learning Solution in the New Normal Era of Community Life - Fitrani Amin; Pandu Adi Cakranegara; Wiwin Ariesta; Joko Joko (HK-Publishing, 2022)
AbstractThis virus disaster has proven to be able to overwhelm almost all the people of the world, especially the people of Indonesia. In addition to having claimed many lives it has also damaged all systems of community life, one of which is the education system. To prevent this pathway from spreading the pandemic, the central government established policies specifically in the field of education which required students to carry out teaching and learning activities carried out at their respective homes online, both at the elementary, junior high, high school, and college level. The High School X educational institution is one of the educational institutions, which was the object of this study, which also experienced the impact of this pandemic and was forced to change its teaching and learning system, namely from offline learning activities and converted into online teaching and learning activities. Also related to the impact of the pandemic on the education system also affects the absence of the National Examination and changes the registration system for new students from High School X who will continue to the next level of education.Keyword: Modernization, Technology, Covid-19 Pandemic, Online AbstrakBencana virus ini terbukti mampu melanda hampir seluruh masyarakat dunia, khususnya masyarakat Indonesia. Selain telah memakan banyak korban jiwa juga telah merusak seluruh sistem kehidupan masyarakat, salah satunya adalah sistem pendidikan. Untuk mencegah jalur penyebaran pandemi ini, pemerintah pusat menetapkan kebijakan khusus di bidang pendidikan yang mewajibkan peserta didik untuk melakukan kegiatan belajar mengajar yang dilakukan di rumah masing-masing secara online, baik di tingkat SD, SMP, SMA, maupun SMK. tingkat perguruan tinggi. Institusi pendidikan SMA X merupakan salah satu institusi pendidikan yang menjadi objek penelitian ini, yang juga mengalami dampak dari pandemi ini dan terpaksa merubah sistem belajar mengajarnya yaitu dari kegiatan pembelajaran offline menjadi pembelajaran online. dan kegiatan belajar. Selain itu terkait dampak pandemi terhadap sistem pendidikan juga berdampak pada tidak adanya Ujian Nasional dan perubahan sistem pendaftaran siswa baru dari SMA X yang akan melanjutkan ke jenjang pendidikan berikutnya.Kata kunci: Modernisasi, Teknologi, Pandemi Covid-19, Daring